ENVIRONMENTAL UNCERTAINTY AS A MODERATOR OF THE INFLUENCE OF PARTICIPATIVE BUDGETING AND BUDGETARY EMPHASIS ON BUDGETARY SLACK IN THREE-STAR HOTELS IN BADUNG REGENCY - Ni Putu Diah Pranaya Kusuma Putri; I Gusti Ayu Made Asri Dwija Putri (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Effective budget management is essential for achieving sound financial performance in 3-star hotels in Badung Regency. However, many hotels struggle to prepare realistic budgets, often resulting in budgetary gaps. Evaluating budgetary gaps is crucial, as they can affect managerial decision-making and negatively impact the hotel's financial performance. This study aims to empirically examine the influence of participatory budgeting and budgetary pressure on budgetary gaps in 3-star hotels in Badung Regency. Furthermore, it analyzes how environmental uncertainty moderates the relationship between participatory budgeting and budgetary pressure with budgetary gaps. The study population consists of 25 three-star hotels in Badung Regency. A purposive sampling technique was employed, with a total of 175 respondents—one manager from each department involved in budget preparation in every hotel. Data were analyzed using SPSS with Moderated Regression Analysis (MRA) techniques. The findings reveal that both participatory budgeting and budgetary pressure have a positive and significant influence on budgetary gaps. Additionally, environmental uncertainty was found to weaken the relationship between participatory budgeting and budgetary gaps but did not moderate the effect of budgetary pressure